The nucleoporin RanBP2 has SUMO1 E3 ligase activity - Pichler, Andrea; Gast, Andreas; Seeler, Jacob S.; Dejean, Anne; Melchior, Frauke (Cell, 2002)
Posttranslational modification with SUMO1 regulates protein/protein interactions, localization, and stability. SUMOylation requires the E1 enzyme Aos1/Uba2 and the E2 enzyme Ubc9. A family of E3-like factors, PIAS proteins, was discovered recently. Here we show that the nucleoporin RanBP2/Nup358 also has SUMO1 E3-like activity. RanBP2 directly interacts with the E2 enzyme Ubc9 and strongly enhances SUMO1-transfer from Ubc9 to the SUMO1 target Sp100. The E3-like activity is contained within a 33 kDa domain of RanBP2 that lacks RING finger motifs and does not resemble PIAS family proteins. Our findings place SUMOylation at the cytoplasmic filaments of the NPC and suggest that, at least for some substrates, modification and nuclear import are linked events.
Gesehen am 13.03.2023